Metode, spesifikasi dan tata cara. Bag: 8 Bendung, bendungan, sungai, irigasi, pantai - [Tidak Terdaftar] (Dep. Pekerjaan Umum, 2002)
Metode, spesifikasi dan tata cara. Bag: 8 Bendung, bendungan, sungai, irigasi, pantai